2006
DOI: 10.1029/2005gl025503
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of radiation budget data provided by the ISCCP and GEWEX‐SRB

Abstract: [1] The projects ISCCP and GEWEX-SRB compute global data sets of radiation budget components at the top of the atmosphere and at the surface. Time series range from July 1983 to June 2001, and to October 1995, respectively. Comparing monthly averages over broader zones we find that the SRB underestimates the incident radiation at TOA by more than 2 -5 Wm À2 over the tropics and up to 40 Wm À2 over polar regions. The ISCCP infrared radiation fluxes near the surface and at TOA, in particular over both polar zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
3
37
0
Order By: Relevance
“…SunDu has been regarded as a measure of cloud cover. However, studies have shown that aerosols can also reduce SunDu (Horseman et al, 2008;Kaiser and Qian, 2002;Raschke et al, 2006;Sanchez-Lorenzo et al, 2008Tang et al, 2011). This paper further demonstrates that SunDu can be used to estimate R s globally with sufficient accuracy to establish its year-to-year variations.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…SunDu has been regarded as a measure of cloud cover. However, studies have shown that aerosols can also reduce SunDu (Horseman et al, 2008;Kaiser and Qian, 2002;Raschke et al, 2006;Sanchez-Lorenzo et al, 2008Tang et al, 2011). This paper further demonstrates that SunDu can be used to estimate R s globally with sufficient accuracy to establish its year-to-year variations.…”
Section: Introductionsupporting
confidence: 55%
“…The inter-annual variation of aerosols was not included. This inter-annual variation can be captured by the observed SunDu (Horseman et al, 2008;Kaiser and Qian, 2002;Raschke et al, 2006;SanchezLorenzo et al, 2008;Sanchez-Lorenzo et al, 2009;Tang et al, 2011). Yang et al (2006) used one year of SunDu data in Japan and R s to derive a 0 , a 1 , and a 2 in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…As a non-dynamic model, the CPTEC-PVM2.0Reg calculates only equilibrium solutions based on long-term mean monthly climate variables. This is done concomitantly by a water balance sub-model using climatological values of surface temperature and precipitation (C. J. Willmott and K. Matsuura, Terrestrial air temperature and precipitation: Monthly and annual climatologies, University of Delaware, Newark, 1998, http:// climate.geog.udel.edu/∼climate/html_pages/archive.html)), intercepted photosynthetically active radiation (I PAR ) (1986( -1995( [Raschke et al, 2006), soil classes [Food and Agriculture Organization of the United Nations, 1991], and atmospheric CO 2 concentration [IPCC, 2007] as inputs.…”
Section: Methodsmentioning
confidence: 99%
“…However, the primary geostationary input to ISCCP H-series is B1U data, which have 3-hourly and ∼ 10 km temporal and spatial resolutions. ISCCP ancillary products have also undergone modifications following recommendations from Raschke et al (2006). Table 1 shows the details of D-to H-series ancillary product changes.…”
Section: Isccp H-series Processingmentioning
confidence: 99%